Intrathoracic kidney in a case of trisomy 18 - Chu, I-Wen; Yeh, Shu-Jen; Lin, Yu-Cheng (The Turkish Journal of Pediatrics, 2008)
We report a case of trisomy 18 (47, XX+18) with intrathoracic kidney. It was discovered incidentally as an opacity at the right lower hemithorax on the chest radiograph, later confirmed by magnetic resonance imaging. Ultrasound can be used as the first-line imaging modality for intrathoracic kidney, even in the prenatal period.